Misinterpreting Section 5(n) of the FTC Act: A Critique of the District Court’s Rulings in FTC v. Kochava - Meal, Douglas (Journal of Law and Commerce, 2025)
In August 2022, the Federal Trade Commission (“FTC”) commenced a lawsuit against Kochava, Inc. (“Kochava”) in the United States District Court for the District of Idaho. The FTC’s lawsuit contains a single count, which claims that Kochava, by its sale of customized geolocation data feeds that allow purchasers of those feeds to identify and track specific mobile device users at “sensitive locations,” is engaged in an “unfair” trade practice towards consumers, in violation of Section 5(a) of the FTC Act. In its press release announcing the lawsuit, the FTC explained the theory of its unfairness claim against Kochava thusly: “Kochava’s sale of geolocation data puts consumers at significant risk. The company’s data allows purchasers to track people at sensitive locations that could reveal information about their personal health decisions, religious beliefs, and steps they are taking to protect themselves from abusers. The release of this data could expose them to stigma, discrimination, physical violence, emotional distress, and other harms.” Commentators immediately recognized that the “unfairness” theory at the heart of the FTC’s lawsuit represented a departure from the FTC’s prior practice of focusing its privacy violation inquiries on whether a company’s data collection practices are “deceptive” towards consumers, due to procedural failures like inadequate privacy notices or a failure to obtain required consumer consents. As such, they rightly characterized the FTC’s action as being a groundbreaking one that could have widespread implications for businesses collecting consumers’ geolocation data, as it had the potential for prohibiting collection of geolocation data outright, rather than merely prohibiting such collection from being done deceptively. And they questioned whether the FTC could meet its burden of proving a Section 5(a) violation based on such collection efforts being “unfair” towards consumers within the meaning of Section 5. The District Court has subsequently rendered two rulings on the legal sufficiency of the unfairness theory being advanced by the FTC against Kochava, the first on May 4, 2023 (“Kochava I”) and the second on February 3, 2024 (“Kochava II” and, jointly with Kochava I, the “Kochava Rulings”). Among other issues, the Kochava Rulings address whether the FTC’s claim against Kochava is affected by Section 5(n) of the FTC Act, the first sentence of which provides that the FTC “shall have no authority under” Section 5 of the FTC Act to declare an act or practice unlawful on the grounds that such act or practice is “unfair” within the meaning of Section 5(a) “unless the act or practice [1] causes or is likely to cause substantial injury to consumers [2] which is not reasonably avoidable by consumers themselves and [3] not outweighed by countervailing benefits to consumers or to competition.” Specifically, the in the Kochava Rulings the District Court ruled that: • An intangible injury such as “invasion of privacy” can constitute “substantial injury” to a consumer within the meaning of Section 5(n)’s first prong. • An act or practice is “likely” to cause an injury to a consumer within the meaning of Section 5(n)’s first prong where it creates a “significant risk” that the consumer will incur that injury. • An act or practice is sufficiently alleged to fail the cost-benefit test inherent in Section 5(n)’s third prong merely by alleging that the cost of safeguards to prevent the consumer injury threatened by the act or practice would be “reasonable.” • Evidence sufficient to satisfy the three prongs of Section 5(n) is in and of itself sufficient to establish that the act or practice in question is “unfair” to consumers within the meaning of Section 5(a). Each of the District Court’s four above-described Section 5(n) rulings embraced an interpretation of Section 5(n) advanced by the FTC and rejected a contrary interpretation advocated by Kochava. Moreover, as described in this article, each of these rulings either represented a “first-ever” judicial ruling on the issue in question or contradicted at least one other prior judicial ruling that had already addressed that issue. As a result it is small wonder that the Kochava Rulings led one leading commentator to remark that the court’s decision “would be a game changer in the consumer protection realm, if it continues to hold water later in this case and across other courts,” and prompted a Democratic-appointed FTC Commissioner to state publicly that the Kochava Rulings’ backing of the unfairness theory advanced by the FTC in Kochava is a “very big deal” for the FTC and in the data privacy community generally. Unfortunately, as discussed in this article, the Kochava Rulings’ interpretations of Section 5(n) of the FTC Act are not only novel but also, at least in this author’s view, incorrect. Those rulings therefore stand as a “potential game changer” and as a “very big deal” for all the wrong reasons. If the District Court’s misinterpretations of Section 5(n) in FTC v. Kochava are upheld in that case as it moves forward and/or are followed in other cases by other courts around the country, the FTC will have achieved a dramatic, albeit legally indefensible, expansion of its unfairness authority under Section 5(a) not only in the consumer data privacy realm but in all other consumer contexts as well. It is vitally important, then, for courts and litigants alike to understand how badly the Kochava Rulings misinterpret Section 5(n), so they can prevent those misinterpretations from taking hold more widely and causing even more mischief than they have already caused for Kochava. This article seeks to provide such an understanding.